Transformation of siege into feelings in the Palestinian cinema - Alraee, Ghada (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
ABSTRACT: The Oslo Accords were seen as a step forward towards the establishment of the independent Palestine. These accords put an end to the First Intifada and led to the creation of the Palestinian National Authority (PNA), which generated a state of hopefulness among the Palestinians generally. Yet, under the ongoing Israeli siege, the PNA has been unable meet the expectations of its citizens. Things have gone from bad to worse, with the outbreak of the Second Intifada in 2000 followed by the bloody confrontations between the political factions Fatah and Hamas in 2007. In the light of such developments, the Palestinian identity has gone through significant transformations, always already in process. This study deals with the complexity of the Palestinian identity. It examines how this identity is (re)constructed in response to the recent developments in Palestine as portrayed in filmic representations. It focuses on the films ―The Salt of This Sea‖ by Annemarie Jacir (2008) and ―Laila's Birthday‖ by Rashid Mashrawi (2008). The events of the first film take place in the West Bank and Israel while the second one is made in the West Bank. These films are analyzed in terms of Israeli-Palestinian relationships and in terms of Palestinian-Palestinian relationships. The study showed the emergence of a nationalist ruling elite in Palestine. This class adopts a pragmatic position regarding the right of return, supporting the citizenship of refugees in the hosting countries. This means that the future Palestinian state will not include all the refugees. This study, also, showed that any experience of return involves a new displacement. It is noticeable that the end of the internal conflict is a recent goal included on the national agenda. Today, the poor tend to affiliate to national factions to get economic aids. Remarkably, the shared experience of siege exposes the fractures that the ―national unity‖ tries to suppress. Moreover, the state of insecurity also originates within the Palestinian society, and is not only caused by Israel. Keywords: national identity, Nakba, Israeli occupation, Palestinians, siege, unity, conflict, lawlessness, right of return, homeland, exile, Intifada, Oslo Accords. ………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Oslo Anlaşmaları bağımsız Filistin‘in kurulmasına yönelik adımlar olarak görüldü. Bu anlaşmalar, Bu anlaşmalar, Filistinlilerin genelinde bir umut havası yarattı, ve Birinci İntifada‘yı sona erdirerek Filistin Ulusal Yönetimi‘nin yaratılmasının yolunu açtı. Ancak Filistin Ulusal Yönetimi, İsrail kuşatması devam ederken vatandaşlarının beklentilerini karşılamakta başarılı olamadı. İkinci İntifada‘nın 2000 yılında patlak vermesi ve bunun akabinde, 2007 yılında, El Fetih ve Hamas arasındaki iç siyasi çatışmanın ortaya çıkmasıyla işler daha da kötüye gitti. Hemen her zaman zaten oluşum halinde olan Filistin kimliği de bu gelişmelerin ışığında önemli dönüşümler geçirdi. Bu çalışma Filistin kimliğinin çetrefil doğası üzerinedir; bu kimliğin Filistin‘deki son gelişmelerle beraber, film temsillerinde nasıl (yeniden) inşa edildiğini incelemektedir. Tez çalışması, şu filmler üzerine odaklanmaktadır: Annemarie Jacir‘in 2008 yapımı ―The Salt of This Sea‖ (Bu Denizin Tuzu) ve Rashid Mashrawi‘nin 2008 yapımı ―Laila‘s Birthday‖ (Laila‘nın Doğum Günü) adlı filmleri. İlk filmdeki olaylar Batı Şeria ve İsrail‘de, ikinci filmdeki olaylar ise sadece Batı Şeria‘da geçmekte; ve bu filmler İsrail-Filistin ve Filistin-Filistin ilişkileri açısından analiz edilmektedir. Çalışma, Filistin‘de milliyetçi bir yönetici elit sınıfının ortaya çıktığını; bu sınıfın geri dönüş hakkı konusunda pragmatik bir pozisyonu benimsediğini göstermektedir. Bu yeni oluşan sınıf, mültecilerin yaşadıkları ülkelerin vatandaşı olmalarını desteklemektedir. Bu demektir ki gelecekteki Filistin Devleti tüm mültecileri kapsamayacaktır. Bu çalışma ayrıca göstermektedir ki her geri dönüş deneyimi yeni bir yerinden edilmeyi içermektedir. İç çatışmanın sona erdirilmesinin ulusal gündemde yer alan yeni bir hedef olduğu ortadadır. Günümüzde ulusal hiziplerle bağlantılar, hızla, grupların ya da kişilerin ekonomik çıkarlarının tatmin edilmesinin bir aracı haline gelmektedir. Ne ilginçtir ki, ulusun yaşadığı kuşatma, bütünleşme yerine toplumsal çözülmeye neden olmuştur. Ayrıca, yaşanan güvensizlik durumunun Filistin toplumunun içinden de kaynaklandığını ve nedeninin sadece İsrail olmadığını da not etmek gerekir. Anahtar sözcükler: ulusal kimlik, hafıza, Nakba, İsrail işgali, Filistinliler, kuşatma, birlik, çatışma, hukuksuzluk, geri dönüş hakkı, anavatan, sürgün, ikinci intifada, Oslo Anlaşmaları.
Master of Arts in Communication and Media Studies. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Communication, Dept. of Communication and Media Studies, 2014. Supervisor: Assoc. Prof. Dr. Tuğrul İlter.
Keywords: Communication and Media Studies; Motion pictures - Cinema - Political Aspects - Palestine; National Identity, Nakba, Israeli Occupation, Palestinians, Siege, Unity, Conflict, Lawlessness, Right of Return, Homeland, Exile, Intifada, Oslo Accords